Filmmakers’ interpretation of environmental science fiction - Gustavsson, Sara (2022)
We are now living within the reality of the worst environmental crisis mankind has ever seen and some modes within environmental communication are struggling to help us create change. In recent decade, there has been a growing interest in using storytelling for sustainable change. Science fiction is seen as a genre of great possibility, and filmmakers and writers within this field have long known of the possibilities provided within this medium because of its ability to travel in time and space. Some scholars and writers argue that storytelling is a powerful way of communicating but the stories are not living up to its promise as they keep telling the same old stories. In this thesis I turn to the filmmakers themselves to ask them about the possibilities and limitations of science fiction storytelling that can lead to behavioral changes and attitudes about the environmental future by researching the following questions: